(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the efficacy of ozone as a supporting therapy in reducing pain, edema, and trismus after lower third molar extraction. The protocol was registered in PROSPERO. Six electronic databases (PubMed, Scopus, LILACS, SciELO, Embase, and Web of Science) were used. Only randomized clinical trials were included, without restriction of year, language, and publication status. The JBI tool was used to assess the risk of bias. The GRADE approach assessed the certainty of evidence. The search yielded 3386 results, from which only three articles were eligible. The studies were published between the years 2013 and 2017, resulting in a sample of 133 patients. Ozone was used in the form of gas or gel. All studies found significant results for pain reduction after one, three, and seven days. Success in reducing trismus and edema varied between studies. The risk of bias varied between moderate and low. All outcomes were classified as a very low level of certainty. Although presenting favorable results for pain reduction, there is insufficient evidence to indicate the use of ozone as a complementary therapy during the extraction of third molars.